The Effect Of Phototherapy (24 Hours) Towards Jaundice Degrees Of The Newborn In Hospital NICU West Nusa Tenggara Province - Rosalia Selung; Indah Wasliah; Eka Adithya Pratiwi (Universitas Muhammadiyah Semarang, 2018)
Background: Aximately 60% of normal birth infant become jaundiced in the first week of birth. The incidence of jaundice in the West Nusa Tenggara hospital in 3 years later (2012-2014) there were 1166 cases. Phototherapy of total serum bilirubin (TSB) increased. Clinical trials have validated the efficacy phototherapy in reducing excessive unconjugated hyperbilirubinemia, and its implementation has been drastically confine the use of exchange transfusion (Bhutani, 2011). Objective:The purpose of this study was to determine the degree of jaundice before and after phototherapy, as well as analyze the influence phototherapy before and after the degree of jaundice in the newborn. Method:This type of research is pre-experimental research design using the approach one group pre-test and post-test design. The study population was all jaundice infants who were treated at Hospital NICU room in West Nusa Tenggara Provence in May 2016. The sample was 15 respondents with acsidental sampling techniques. The method of data analysis with descriptive percentage univariate and bivariate analysis with test of rank correlation test (spearman) obtained significance value p = 0.000 < 0.05 and spearman correlation coefficients obtained by value p = 0.025 which means there is a strong correlation between the influence of phototherapy (24 hours) the degree of jaundice in the newborn. Result: The results were obtained degree of jaundice before phototherapy is as many as 9 degree 4 respondents (60%) and as many as 6 degrees five respondents (40%). After 24 hours phototherapy all respondents decreased the degree of jaundice and most have some degreen of jaundice 3 of 10 respondents (66,7%) by 5 respondents (33,3%). Discussion:Recommendations can be given is a gift phototherapy to decrease the degree of jaundice.